Synthetic anti-lipopolysaccharide peptides and hepatitis C virus infection. (November 2013) - Habersetzer, François; Leboeuf, Céline; Doffoël, Michel; Zeisel, Mirjam B; Baumert, Thomas F
<x xml:space="preserve">Abstract</x> Introduction: Hepatitis C virus (HCV) infection is a leading cause of cirrhosis and hepatocellular carcinoma. Although antiviral therapy has been markedly improved by the licensing of direct-acting antivirals, safety, resistance, high costs and difficult-to-treat patients remain important challenges. Areas covered: This article focuses and comments on the recent development of synthetic anti-lipopolysaccharide peptides (SALPs) which bind to highly sulfated glycosaminoglycan/heparan sulfate (HS) on cell surface. HS serves as a primary docking site for several viruses to their respective host cells before the viruses interact with their cell surface receptor(s). In vitro studies have shown that SALPs inhibit entry of HCV without cell toxicity. Expert opinion: SALPs prevent viral infection in cell culture model systems. Treatment studies of established HCV infection in cell culture models as well as proof-of-concept and safety studies in animal models are needed to evaluate their potential for drug development. The mechanism of action of SALPs as entry inhibitors suggests a potential application for HCV-infected patients to prevent reinfection of the liver graft in liver transplantation. Potential limitations may include high doses to obtain an antiviral effect and a target which is widely expressed and has a key function in cell physiology.